Persepsi Mahasiswa Keperawatan Dalam Menjalani Osca Komprehensif Di Universitas Muhammadiyah Surakarta - Fajriyah, Nurul; , Enita Dewi, S.Kep., Ns, MN (2016)
Comprehensive OSCA is an evaluation method that can be applied in clinical or academic settings. The comprehensive OSCA can also be used as a tool to evaluate students' competence including of cognitive, affective, and psychomotor. However, this method also has weaknesses that can affect the psychological condition and impact on students' failure. Students' perceptions of comprehensive OSCA will affect students' thought, judge and to something as well as how they learn result in students' learning outcomes. This research aims to describe and analyse the students' perceptions about of comprehensive OSCA. This is quantitative descriptive research using cross sectional study. The sample in this study 68 students (semester two and four) selected using stratified random quota. Data collection uses questionnaire with likert scale. The results from this study are the perception of students' about their preparation and implementation of comprehensive OSCA in category, medium with 72.1% and 89.7%, respectively. While the students' perceptions on the impact and sustainability of comprehensive OSCA in both categories with 66.2% and 77.9%, respectively. Students' are less to prepare well before undergoing the comprehensive OSCA. Students also perceive comprehensive OSCA can provoke anxiety. The comprehensive OSCA can improve skills, and students' continue to use the comprehensive OSCA at UMS as a method of evaluating the skills of nursing students'. This study comprehensif can improve skills but it couses students' concludes that the anxiety. Comprehensive OSCA can be modified by having a previous trial, giving feedback immediately and having camera recorder to reduce student anxiety when performing their action.